Successful wound healing over exposed metal implants using vacuum‐assisted wound closure in a dog. (8th April 2013) - Bertran, J.; Farrell, M.; Fitzpatrick, N.
<x xml:space="preserve">Abstract</x> An eight‐month‐old Labrador retriever was presented with a grade IIIb open shearing injury of the left tarsus. Acute severe surgical site infection developed 2 days after pan‐tarsal arthrodesis, resulting in wound dehiscence. Vacuum‐assisted wound therapy was carried out for 12 days to treat an extensive full‐thickness soft tissue defect with exposure of metal implants. New granulation tissue formation covering most of the defect was achieved by day 10 of this therapy. Epithelialization was achieved by second intention healing with open wound management. To the authors' knowledge, this is the first veterinary clinical case report documenting complete healing over exposed metal implants without any requirement for surgical revision.